Veenhoven vs. Easterlin in Happiness Economics: Does Economic Growth Increase Happiness? - Hatime Kamilçelebi (İktisat Politikası Araştırmaları Dergisi)
Richard Easterlin was one of the pioneers of happiness economics studies and stated in his studies that a significant correlation exists between happiness and per capita income. He also explained that, despite the occurrence of an increase in per capita income in the countries he’d studied in his work, no increase had occurred in the stated happiness levels, with the average happiness level in rich countries not being higher than in poor countries. This result is called the Easterlin Paradox in the literature. Ruut Veenhoven was another pioneer of happiness economics and replied to the contradictory results in Easterlin’s study on economic growth and happiness. Veenhoven later criticized the empirical results of Easterlin’s research by using the same data that Easterlin had used and comparing with the results from other studies. Veenhoven (1989) stated an increase in per capita income to increase that country’s happiness levels. As a response to Veenhoven, Easterlin maintained the view that no long-term correlation exists between economic growth and happiness in his scientific studies. However, Veenhoven stated that his studies on the subject so far and the results tested with data from many countries had revealed the opposite. According to Veenhoven, the Easterlin Paradox is an illusion rather than a rule. These discussions from both happiness economics pioneers form the cornerstones of the happiness economics literature. The aim of the study is to examine in detail the works and research of Easterlinand Veenhoven that occurred in response to one another while simultaneously explaining the relationship betweeneconomic growth and increase in happiness in countries using the results from their works. When comparing the findings obtained from the data used by both scientists, happiness has been concluded to increase more in poor and developing countries as per capita income increases than in developed countries, although some countries were seen to be exceptions.